Relation between physicochemical characteristics and sensory profiles of cooked pumpkin varieties - R.V. Santana, D.S. Lima, A.B. de Almeida, T.M. de Lima, J.G. de Oliveira Filho; Moreira, E.A.; Egea, M.B. (Emirates Journal of Food and Agriculture, 2019)
Since pumpkin is a widely consumed vegetable in the human diet, this study aimed to evaluate the relation between physicochemical characteristics and sensory profiles of pumpkin varieties. Samples were coded as follows: PS is the scented pumpkin (PS01, PS02, PS03), MP is the moranga pumpkin (MP01), HP is the hybrid pumpkin (HP02, HP03, HP12), and CP is the commercial hybrid Tetsukabuto pumpkin. Pumpkin varieties were evaluated as to total titratable acidity, pH, soluble solids, carotenoid content, cooking time, color, hardness, descriptive sensory analysis, preference, and purchase intention (affective sensory analysis). Consumers’ profiles were evaluated by an online questionnaire. The highest values of total soluble solids and scores for sweet taste in the sensory evaluation were shown by PS02 and CP. The former exhibited the highest carotenoid content (172.88 mg 100g-1) while the hybridization process resulted in pumpkins (HP02, HP03 and HP12) with the lowest total carotenoid content (50.94-51.90 mg 100g-1). All pumpkin varieties were mostly yellow (positive b* value). The consumers’ profile shows their preference for small fruits (mass between 1.0 and 1.5 kg) that are peeled and whose pulp is orange. Association between the descriptive test and the preference one showed that orange pumpkins were prefered by the sensory panel. The sensory profile and physicochemical characteristics are important tools to the production of hybrids and breeding of genetic pumpkin varieties. This is a field of research that has grown lately and may result in higher productivity and quality of this vegetable.